Sonography in Acute Ureteric Colic: An Experience in Dhulikhel Hospital - Joshi, KS; Karki, S; Regmi, S; Joshi, HN; Adhikari, SP (Kathmandu University Medical Journal, 2015)
Background Computed tomography is considered as an imaging modality of choice in acute ureteric colic. However due to concerns regarding radiation exposure, sonograms are re-emerging as imaging methods in such situations. Objectives To evaluate the role of sonography in detection of calculus in acute ureteric colic. Methods Total 384 patients were enrolled. Hydronephrosis was graded as mild, moderate or severe. Calculus was detected as an intraluminal echogenic focus with distal shadowing with twinkling artifact. Number, size and position of the calculi were assessed. Patients were categorized into four groups:I. ureteric colic only II. ureteric colic with hematuria III. ureteric colic with hydronephrosis and IV. ureteric colic with hematuria and hydronephrosis and then the possibility of detection of calculi has been compared among these groups. Results Out of 384 patients, 254 were found to have calculi ranging between 2.7-27mm. Nineteen had in the pelvis/ pelviureteric junction, 64 in proximal ureter, 125 in distal ureter, 6 at iliac crossing and 40 at vesicoureteric junction. Two hundred forty one had single and 14 had multiple calculi. Calculus detection is easier in category III and IV patients. The sensitivity and specificity of ultrasonography were 87.98% and 93.07%. Degree of hydronephrosis is strongly correlated with the number of calculi but weakly correlated with the size of the calculus. Conclusion Sonogram can be used in all cases of acute ureteric colic. Hydronephrosis is the most important finding because it paves the way out for the detection of calculus. Kathmandu University Medical Journal Vol.12(1) 2014: 9-15